Discussions on the Adsorption Behaviors Affected by the Differences Between Graphene Oxide and Graphene Grafted by Chitosan - Chin-Chun Chung; Hua-Wei Chen; Jin-Lin Han; Hung-Ta Wu (Polysaccharides)
There are limited studies in the literature on the surface characterization of modified graphene and graphene oxide and the impact of these modified adsorbents on adsorption performance. In addition, the amine group essentially has a promising affinity for carbon dioxide (CO2). Therefore, chitosan was used in this study to be grafted onto graphene and graphene oxide respectively. This study examines the effects of graphene, graphene oxide, and chitosan-modified graphene oxide thin films on the removal of carbon dioxide (CO2). Thin films of graphene, graphene oxide, and their chitosan-modified counterparts were prepared via the methods of precipitation and grafting. The differences in the chemical structure, surface properties, and surface morphology of the films were evaluated, and their effect on the adsorption performance of CO2 is discussed herein. The micrographs from a scanning electron microscope (SEM) show that the surface of graphene oxide appeared to be more porous than graphene, and the amount of grafted chitosan on graphene oxide is higher than that on graphene. An analysis of atomic force microscope (AFM) finds that the surface of chitosan-modified graphene oxide is rougher than that of chitosan-modified graphene. The results of energy-dispersive X-ray spectroscopy (EDS) spectra reveal that the composition of oxygen in graphene oxide is greater than that in graphene and confirm that the oxygen and nitrogen contents of chitosan-modified adsorbents are greater than those of the pristine materials. An analysis of Fourier-transform infrared spectroscopy (FTIR) shows that most of the oxygen-containing groups are reacted or covered by amide or amine groups due to modification with chitosan. The adsorption isotherms for CO2 adsorbed by the prepared graphene and graphene oxide presented as type I, indicating great adsorption performance under low pressure. The appropriate amount of chitosan for modifying graphene oxide could be found based on the change in surface area. Although the breakthrough times and the thicknesses of the mass transfer regions for graphene oxide modified with 0.9% and 1.2% chitosan were similar, the modification of graphene oxide with 0.9% chitosan was appropriate in this study due to a significant decrease in surface area with 1.2% chitosan dosage. The adsorption uptake difference between chitosan-modified graphene oxide and graphene was greater than that without modification with chitosan due to more chitosan grafted on graphene oxide. The Toth adsorption isotherm model was used to fit the adsorption uptake, and the average deviation was about 1.36%.